Unraveling Firm Value Dynamics: The Moderating Role of Media Exposure in ESG, Leverage, and Capital Structure - Nasution, Mario Zulfa; Adwimurti, Yudhistira; Rahmani, Hani Fitria (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study aims to analyze the effect of capital structure, leverage, and Environmental, Social, and Governance (ESG) on firm value, as well as the moderating role of media exposure in cyclical and non-cyclical companies listed on the Indonesia Stock Exchange in 2023. Using a quantitative research design with a cross-sectional approach, this study took a sample of 150 companies through a purposive sampling method. Data analysis was carried out using multiple linear regression with moderating variables. The results of the study indicate that capital structure and ESG have a significant positive effect on firm value, while leverage has a significant negative effect. Media exposure is proven to significantly moderate the relationship between all independent variables and firm value. These findings emphasize the importance of optimizing capital structure, prudent leverage management, and implementing good ESG practices in increasing firm value. The moderating role of media exposure highlights the importance of a company's communication strategy in shaping public and investor perceptions. The implications of this study provide valuable insights for company managers in making strategic decisions and for investors in evaluating investment prospects in the Indonesian capital market.